Maximizing ion accessibility in MXene-knotted carbon nanotube composite electrodes for high-rate electrochemical energy storage - Xiang Gao (Nature Portfolio, 2020)
Improving the accessibility of ions in the electrodes of electrochemical energy storage devices is vital for charge storage and rate performance. Here, the authors report a new type of MXene-carbon nanotube composite electrode that maximizes ion accessibility, resulting in high rate performance at low temperatures.